Humanitarian Facts In Fahad Alammari’s Film Alkhallat+: A Study Of Lucien Goldmann's Genetic Structuralism - Nur Azizah Arifin; Maman Abdul Djaliel; Muhammad Nurhasan (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
The film Alkhallat+ by Fahad Alammari is a social reflection of modern Saudi Arabian society, rich in human values. This study aims to analyze aspects of humanity, both individually and socially, using Lucien Goldmann's genetic structuralism theory. The method used in this study is descriptive qualitative, with a dialectical analysis technique between the structure of the film text and the social context of contemporary Arab society. Previous studies show that the film Alkhallat+ a study of lucien goldmann’s genetic structuralism has been analyzed through various approaches, such as structural functionalism, pragmatics, and gender deconstruction. However, there has been no study that specifically focuses on the human aspects within the framework of genetic structuralism. Therefore, this study makes an original contribution by revealing the relationship between the individual conflicts of the characters and the collective worldview of society. The results of the study show that this film contains human facts that include moral conflicts, family tensions, gender bias, and social pressures that represent the reality of modern Arab society.